The parasite density and erythrocyte sedimentation rate on patients with uncomplicated tropical Malaria In two community health centre of West Lombok - Kadeq Novita Prajawanti; Siti Zaetun; Pancawati Ariami (Department of D3 Medical Technology Laboratory STIKes Hutama Abdi Husada Tulungagung, 2019)
Malaria infections are often associated with the activation of coagulation and fibrinolytic systems. An increase number of fibrinogen levels in severe malaria and the increase of fibrinogen also stimulated the increase of erythrocytes sedimentation rate. The aim of this study is to find out about the effects of high parasitemia to erythrocyte sedimentation rate in patients with uncomplicated tropical malaria. Samples are collected using the Purposive Samplings method. To determined the effect of parasite density to erythrocytes sedimentation rate (ESR) levels (mm/h), the data were analyzed using the Non-Parametric Kruskal Wallis test (α=0,05). From 8 samples, 2 subjects (25%) has ++ (2+) densities with 35 and 46 mm/h; 3 subjects (37,5%) has +++ (3+) densities with 10, 65 and 70 mm/h; and also 3 other subjects (37,5%) has ++++ (4+) densities with 21, 44, and 70 mm/h. The Non-parametric Kruskal Wallis test shows that p-value 0,932 >α, means there is no effect of parasitic density on ESR levels in patients with uncomplicated tropical malaria. Using the ESR as the only-main biomarker in assessing the severity of malaria is an inaccurate idea because the ESR is more likely a non-specific test, therefore another blood test is needed to establish a diagnosis of malaria severity.